Blended-Learning Berbasis Guided-Inquiry Pada Mata Kuliah IPS di Era Pandemi - Mulyani, Pamungkas Stiya; Fuadi, Salis Irvan (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2021)
The purpose of this research is to find out how to prepare learning as a solution for social science lectures during a pandemic, providing an overview for educators to provide effectively and solution learning. This research uses a type of classroom action research by adopting the McKerman model with the research stages: Stages of Problem Description, Needs Analysis, Hypothesis of ideas, Action Plan, Plan Implementation, Evaluation, Decision Making, Stages of Conclusion, and Publication. It is concluded that the instrument has been tested for validation by an expert validator and received input and revision orders by the validator and everything has been done and has been declared valid with very good criteria. This has an impact on the results of student responses wherein the second cycle has increased.